Manajemen Pengelolaan Wakaf (Studi di Bidang Penyelenggara Zakat dan Wakaf Kementerian Agama Kabupaten Kudus) - Muhadirin (Universitas Muria Kudus, 2026)
This study examines waqf management at the Zakat and Waqf Administration Division of the Ministry of Religious Affairs in Kudus Regency. Using a field research approach, data were collected through observation, interviews, and documentation, and analyzed qualitatively through data reduction, display, and conclusion drawing. The study explores waqf management patterns and the factors that support and inhibit them. The findings indicate that waqf management remains largely conventional and stagnant, primarily because Nazhir’s limited understanding of productive waqf leads waqf to be viewed mainly as a religious practice rather than an economic instrument. As a result, many waqf assets, especially land, remain unproductive. The selection of Nazhir based on social trust rather than professional competence also contributes to this issue. Additional obstacles include low public awareness of the legal aspects of waqf and limited qualified human resources. Supporting factors include institutional support, increased legal awareness, and Nazhir's training programs. The managed waqf types include waqf khairi and waqf syuyu’ in the form of land, buildings, transportation facilities, and cash waqf, although cash waqf management is not yet optimal.